2012
DOI: 10.22605/rrh2139
|View full text |Cite
|
Sign up to set email alerts
|

TB questions, East Kwaio answers: community-based participatory research in a remote area of Solomon Islands

Abstract: A licence to publish this material has been given to James Cook University, http://www.rrh.org.au 2Results: Four interviews and a focus group of 12 key informants were conducted and a mountain hamlet with a history of TB was visited. The results represent the data from the interviews and the focus group. The time delay in presenting to the Hospital from when participants first became unwell ranged between two and three years. In the mountain hamlet, two additional people with probable TB were seen who had not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Studies that received ‘poor’ ratings for ethics/bias did not state ethics [ 32 – 34 ] and/or limited their discussions of bias related to methods and data collected. Some studies used convenience or purposive samples [ 3 , 32 , 35 , 36 ] and others required more sampling [ 28 , 34 , 37 – 39 ], which impacted the bias, transferability, and generalizability of results. Remoteness and heterogeneity of Indigenous communities within and across regions is an additional limitation to generalizing results from observational studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies that received ‘poor’ ratings for ethics/bias did not state ethics [ 32 – 34 ] and/or limited their discussions of bias related to methods and data collected. Some studies used convenience or purposive samples [ 3 , 32 , 35 , 36 ] and others required more sampling [ 28 , 34 , 37 – 39 ], which impacted the bias, transferability, and generalizability of results. Remoteness and heterogeneity of Indigenous communities within and across regions is an additional limitation to generalizing results from observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…2 A forest plot that describes the distribution of estimate types related to time to diagnosis and/or treatment of TB among Indigenous peoples across literature included in the systematic review. a) Acronyms: pulmonary TB (PTB), smear positive pulmonary TB (S + PTB), and pulmonary and extrapulmonary TB (PTB & EPTB), b) Distribution was reconstructed to determine the interquartile range, median, and/or range values [ 30 , 32 , 35 ], c) Interval with no point estimate, represents a range [ 31 , 32 , 36 ], and d) Interquartile ranges were used to describe the spread for median values except in Basa et al and Hussen et al [ 37 , 41 ], which was reported as a range …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations